2020
DOI: 10.1002/esp.4871
|View full text |Cite
|
Sign up to set email alerts
|

Reducing systematic dome errors in digital elevation models through better UAV flight design

Abstract: It is well established that digital elevation models (DEMs) derived from unmanned aerial vehicle (UAV) images and processed by structure from motion may contain important systematic vertical errors arising from limitations in camera geometry modelling. Even when significant, such ‘dome’‐shaped errors can often remain unnoticed unless specific checks are conducted. Previous methods used to reduce these errors have involved: the addition of convergent images to supplement traditional vertical datasets, the usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
85
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 37 publications
(73 reference statements)
10
85
1
Order By: Relevance
“…However, their study area was limited to 300 × 70 m of flat topography. It is notable that errors arising from flight designs with crossed strips of convergent imagery, used in our Feshie investigation, yielded similar dome sizes to single and cross strip POI imagery [45]: Table 5. To avoid systematic errors for small survey areas, users should consider POI flight designs.…”
Section: Flight Design and Systematic Errormentioning
confidence: 71%
See 4 more Smart Citations
“…However, their study area was limited to 300 × 70 m of flat topography. It is notable that errors arising from flight designs with crossed strips of convergent imagery, used in our Feshie investigation, yielded similar dome sizes to single and cross strip POI imagery [45]: Table 5. To avoid systematic errors for small survey areas, users should consider POI flight designs.…”
Section: Flight Design and Systematic Errormentioning
confidence: 71%
“…The results of this study coupled with Taddia's [41] demonstrate the applicability of a double grid flight plan for high resolution topographic survey of elongate geomorphic features, such as a coastline or a river corridor. However, Sanz-Ablanedo et al [45] and James et al [11] note that oblique images taken at an angle of 15 degrees or less are suboptimal due to the fact they are more likely to cause surface deformation errors such as doming effects. These studies also found surface deformation to be more pronounced when surveying low-relief topography.…”
Section: Flight Design and Systematic Errormentioning
confidence: 99%
See 3 more Smart Citations